DETERMINATION OF SOME HEAVY METALS IN FORAGE GRASSES IN ZUNGERU NIGER STATE, NORTH CENTRAL, NIGERIA - Usman, M.A; Salawu, Y; Yakasai, I. A.; Bello, I.; Awwalu, S.; Mailafiya M. M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2017)
The serious indiscriminate local gold mining activities in Zungeru communities by the inhabitants led to possible environmental pollution particularly by heavy metal such as, Zinc, Copper, Lead, Nickel and Arsenic. These heavy metals were transported, dispersed and accumulate in plants being grown in that area and fed on by the grazing animals and these animals forms part of human diet as main source of protein. The study aimed at determining the concentrations of these metals in forage grasses being grazed by cattle around Zungeru area of Niger state, North central Nigeria and compared to European Union standards for these metals in forage grasses. Samples were collected at five different grazing pastures sites around the town and analyzed after wet digestion for levels of the heavy metals by atomic absorption spectrometry. The trend of the metal levels was Pb> Ni > As. The mean concentrations obtained in mg/kg were in the range of 4.643± 1.02 to 18.434±1.56 for Lead, 1.534±0.68 to 2.690±0.56 for nickel and 0.304±106 to 0.655±0.05 for Arsenic. Forage grasses examined in this study are relatively not safe for grazing by animals due to high forage lead level. Consumption of such levels may result to risk to public health.